Condylar Asymmetry in Children with Unilateral Posterior Crossbite Malocclusion: A Comparative Cross-Sectional Study - Alessandro Tortarolo; Rossana Rotolo; Ludovica Nucci; Michele Tepedino; Vito Crincoli; Maria Grazia Piancino (MDPI AG, 2022)
Unilateral posterior crossbite (UXB) is a common, severely asymmetric malocclusion, characterized by maxillary hypoplasia and masticatory dysfunction. The aim of this research is to evaluate the asymmetry of mandibular condyles and rami in children with UXB. This comparative cross-sectional study included 33 children with UXB (girls = 15, boys = 18; mean age ± SD = 8.0 ± 1.3 years.months]) and 33 age- and gender-matched controls (girls = 15, boys = 18; mean age ± SD = 8.4 ± 1.3 years.months]). Pre-treatment OPGs were analyzed by comparing the height of condyles and rami between the sides using the method by Habets et al. (1988); the result was considered significant if the degree of asymmetry was >6%. Children with UXB showed a significantly increased asymmetry of mandibular condyles (mean ± SD = 10.7% ± 9, p < 0.001), but not of rami (mean ± SD = 1.9% ± 2.3), compared to controls. The rami did not show significant asymmetry in either group. The presence of an increased condylar asymmetry index in a developing patient with unilateral posterior crossbite is a sign of altered skeletal growth and should be considered in the diagnostic process and treatment plan.